OWNERSHIP STRUCTURE AND FEMALE INCLUSION OF LISTED FINANCIAL FIRMS IN NIGERIA - Gbemigun Catherine Omoleye; Alade Muyiwa Ezekiel (Gusau Journal of Accounting and Finance, 2024)
The study investigated how ownership structure influence the female inclusion of listed financial firms in Nigeria. Using Longitudinal research design findings revealed that managerial ownership exhibited a direct effect on female inclusion, institutional ownership was significant with a direct nexus with female inclusion, while foreign ownership was non-significant but exhibited an inverse sign. The study concluded that share possession held by managers, as well as, other institution that manage people’s wealth determine the percentage of women that participate in board of directors of listed financial firms in Nigeria; while, low share possession held by foreign ownership reduces it. The study recommended that the director within the listed financial firms should ensure that they make their ownership stakes (shares) attractive for foreign ownership through publicity.